2017
DOI: 10.1159/000478050
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes for Metastatic Melanoma of Unknown Primary in the New Era: A Single-Institution Study and Review of the Literature

Abstract: Background: Metastatic melanoma of unknown primary (MUP) is uncommon, biologically ill defined, and clinically understudied. MUP outcomes are seldom reported in clinical trials. In this study, we analyze responses of MUP patients treated with systemic therapy in an attempt to inform treatment guidelines for this unique population. Methods: New York University (NYU)'s prospective melanoma database was searched for MUP patients treated with systemic therapy. PubMed and Google Scholar were searched for MUP patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…In this large population‐based study, we reported the OS for patients with MUP since the introduction of immunotherapy and targeted therapy. A recent small, single‐center study has also evaluated survival in patients with MUP who received novel therapy and showed that 23 patients had a median OS of 9 months after initiating immunotherapy . In an accompanying systematic review, the authors only identified three other papers reporting on patients with MUP who received immunotherapy (a phase II study, a retrospective cohort study, and one case report) and seven papers concerning targeted therapy (six case reports and one small prospective observational study reporting on one patient).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this large population‐based study, we reported the OS for patients with MUP since the introduction of immunotherapy and targeted therapy. A recent small, single‐center study has also evaluated survival in patients with MUP who received novel therapy and showed that 23 patients had a median OS of 9 months after initiating immunotherapy . In an accompanying systematic review, the authors only identified three other papers reporting on patients with MUP who received immunotherapy (a phase II study, a retrospective cohort study, and one case report) and seven papers concerning targeted therapy (six case reports and one small prospective observational study reporting on one patient).…”
Section: Discussionmentioning
confidence: 99%
“…While clinical trials of novel therapy have included patients with MUP, the outcomes in these patients have not been reported specifically . Given the potential difference in biology compared to MKP, knowing the outcomes during novel therapy for patients with MUP could aid clinical decision‐making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Once melanoma has spread into the lymph nodes, or even visceral organs and the brain, it remains a life-threatening disease despite the advent of molecular targeted or immunotherapies. 1,2 Melanoma of unknown primary (MUP) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] represents an unusual subtype of melanoma which was reported to be about 2-9% of melanoma of known primary (MKP) at all stages. 3 Some of the literature in the different geographic regions demonstrated better overall survival of MUP than of MKP.…”
Section: Introductionmentioning
confidence: 99%
“…15 Other publications, however, reported an equal or even worse clinical outcome for patients with MUP when compared to MKP with comparable stage of disease. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Hence, the prognosis of patients with MUP compared to MKP patients is still unclear and likely depends on the clinical scenario investigated. A 5-year overall survival rate of MUP before the era of the immune checkpoint inhibitor was reported to range from 8% to 18% with the most common metastatic sites in lymph nodes and gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%